PENGGUNAAN SEKURITAS TERSEDIA UNTUK DIJUAL DALAM MANAJEMEN LABA DAN MANAJEMEN RASIO KECUKUPAN MODAL - sungkowo, wulandari (PRISMAKOM, 2024)
The purpose of this study is to examine whether Indonesian bankings practice earning and capital adequacy ratio management using available for sale- securities. Samples were 30 banks selected by purposive sampling method from conventional banking companies listed in Indonesia Stock Exchange during the observation period 2011-2013. This study use two multiple linear regression models. The first model is about to detect bank manager use available for sale-securities to manage earning. Meanwhile, the second model is about to detect bank manager use available for sale-securities to manage capital adequacy ratio. The results of this study indicate that manager using available for sale-securities to manage earnings. However, manager doesn't use available for sale-securities to manage capital adequacy ratio. These findings indicate that managers use sale of available for sale securities to manage earning in bank.